Implementation of the Regulations for Preventing Collisions at Sea (P2TL) in the Implementation of Watch Duty When Entering Narrow Shipping Channels to Prevent the Hazard of Collisions on the SPB Lais Ship - Rheza Wicaksana Adji; Anugrah Nur Prasetyo; Dyah Ratnaningsih; I’ie Suwondo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the implementation of the Collision Prevention Regulations (P2TL/COLREG) in the implementation of watchkeeping when entering a narrow channel on board the SPB Lais, motivated by the risk of collision in restricted waters and the incident that occurred on May 22, 2025. The objectives of the study are to describe P2TL compliance during watchkeeping, identify efforts to optimize P2TL implementation, and evaluate compliance with STCW provisions on watchkeeping. This study uses a single case study design with a descriptive qualitative approach. The population is the SPB Lais bridge personnel during the researcher's sea practice; purposive sampling selected the captain, watch officer, helmsman, and several crew members as informants. Instruments include standardized observation sheets, semi-structured interview guidelines, and logbook documents and standing orders; data analysis was carried out through data reduction, thematic coding, triangulation, and iterative presentation following the Miles and Huberman method. The results demonstrate significant implementation of P2TL principles such as continuous lookout, utilization of radar, AIS, and ECDIS, standardized VHF communications, safe speed, and engine readiness for maneuver; however, residual vulnerabilities are identified in the form of environmental influences on vessel maneuvers, delayed decision-making in critical situations, and signs of crew fatigue. The distinction between the results and conclusions is emphasized: the results present empirical findings on compliance and operational weaknesses, while the conclusions recommend strengthening handover procedures with checklists, bridge resource management exercises, and fatigue management policies to improve the effectiveness of P2TL in narrow channels. Practical implications include procedural and training recommendations that can be immediately implemented to reduce the risk of collision.